DAMPAK PENAMBANGAN BAHAN GALIAN GOLONGAN C TERHADAP KERUSAKAN LAHAN DISEPANJANG PINGGIR BATANG SULITI DI KECAMATAN SUNGAI PAGU KABUPATEN SOLOK SELATAN - SEFIANI, VINA; Edial, MT, Drs. Helfia; Putri, S.Pd, M.Si, Rozana Eka (Pendidikan Geografi, 2014)
ABSTRACTÂ This study is devoted to the Batang Suliti in Sungai Pagu Kabupaten Solok Selatan Â order to determine the impact of land degradation that caused the river bank mining minerals group C. The method used is descriptive. Samples were taken by using purposive sampling technique that is based on the presence of mineral mining group C which caused damage along the flow Suliti land. The study concluded that: 1) The impact of mineral mining group C against the cliff slope conditions (slope, vegetation cover, soil texture, buffer erosion) along the side of Batang Suliti in Sungai Pagu Kabupaten Solok Selatan, river bank erosion on the riverbank due in part steep, vegetation cover changes of paddy land becomes scrub and mixed farms, changes in soil texture, especially for areas that do not have a concrete buffer buffer such as erosion, 2) Impact of mining excavation category C is the damage to the farmland where the sample damage occurred about 0,3 ha, on a sample of 2 to 0,9 ha and extensive damage to the samples 3 damage that occurs in 0,8 hectares along the Batang Suliti. This shows the narrowing of the agricultural land on the side of Batang Suliti flow due to mining activities excavation category C requires large areas. Additional damage occurred on land owned plantations and rice fields in the surrounding watershed communities, where gardens and fields turned into a place of mining and quarrying category C, 3) the impact of mining activities Class C excavation impact on groundwater conditions in the area along the river, the color of murky water, fishy smell and sour taste, whereas groundwater in the river Batang Suliti utilized as a source of public toilets byÂ